Analisis Kesulitan Belajar Matematika Siswa Kelas II Pada Materi Nilai Tempat di SDN Gayamsari 01 Semarang - Mila Nur Afifah; Ary Susatyo N; Muhammad Arief Budiman (STKIP Andi Matappa Pangkep, 2022)
Mathematics learning in elementary school is a subject that must be studied by students. Mathematics has benefits that students can feel for themselves, especially in students' lives. Students of SD N Gayamsari 01 have difficulty writing number symbols, understanding place values, and difficulty in arithmetic operations. The purpose of the study was to describe what learning difficulties were experienced by class II students in the place value material at SD N Gayamsari 01 Semarang and to describe what factors caused learning difficulties for class II students in the place value material at SD N Gayamsari 01 Semarang. Collecting data obtained by observation, tests, interviews and documentation.The difficulties experienced by the second grade students of the Gayamsari State Elementary School in the place value material, namely errors in accuracy, understanding the concept and the calculation process. Factors that cause student difficulties are caused by internal and external factors. Internal factors of students include intellectual and emotional factors such as self-confidence, interest in learning and motivation to learn. While the external factors of students include the teacher's clarity in explaining, class conditions and family environment.